Models of Conduct of Russian Federation in International Conflicts in 1990-2000 s. - A. A. Sushentsov (Vestnik MGIMO-Universiteta)
The article clarifies author’s typology of conflict behavior in contemporary international conflicts proposed in previous papers. Based on the methodology of analysis of the motives for conflict behavior the paper contains a classification of the most significant international conflicts 1990-2000's with the participation of Russia. In conclusion are given the results of an in-depth analysis of the Georgian- South Ossetian conflict in 2008, with an emphasis on analyzing the behavior of Georgia, Russia and the United States.